Rapid Measuring Flavor Quality Changes of Frying Rapeseed Oils using a Flash Gas Chromatography Electronic Nose. Issue 5 (7th March 2019) - Xu, Lirong; Li, Xu; Huang, Jianhua; Gao, Pan; Jin, Qingzhe; Wang, Xingguo
Abstract : A flash gas chromatography electronic nose (FGC E‐nose) is applied to measure flavor quality changes and monitor the oxidation process of rapeseed oils during frying. Partial least squares regression (PLS) is applied to determine the relationship between total polar compounds (TPC) and some volatile compounds determined by FGC E‐nose in frying rapeseed oils. Qualitative differentiation between frying oil samples with different frying time is analyzed by principal component analysis (PCA) and hierarchical cluster analysis (HCA). The PCA and HCA results show that the FGC E‐nose could be used to discriminate oil samples with different frying time. The results show a good linear relationship ( R 2  = 0.98; SD = 1.433) between TPC in oil samples measured by AOCS method and that predicted by the FGC E‐nose responses using PLS method. Thus, this study indicates that the FGC E‐nose method could be available for rapid at‐ or on‐line implementation in oxidation control of frying oils. Practical Applications : Standard methods for determining the TPC of frying oil samples are labor‐intensive and require toxic chemicals. The volatile compounds determined by FGC E‐nose show a good linear relationship with TPC in frying rapeseed oil samples. The FGC E‐nose technique is suitable to monitor the frying process and the proposed method has the potential to be a more rapid and convenient tool for quality control of frying oils. A flash gas chromatography electronic nose (FGC E ‐nose) is applied to measure flavor quality changes and monitor the oxidation process of rapeseed oils during frying. Partial least squares regression is applied to determine the relationship between total polar compounds and some volatile compounds determined by FGC E‐nose in frying rapeseed oils. Abstract : A flash gas chromatography electronic nose (FGC E ‐nose) is applied to measure flavor quality changes and monitor the oxidation process of rapeseed oils during frying. Partial least squares regression is applied to determine the relationship between total polar compounds and some volatile compounds determined by FGC E‐nose in frying rapeseed oils.